Mathematical temperature simulation in tool-to-work contact zone during metal turning - E. V. Bordatchev; V. P. Lapshin (Advanced Engineering Research, 2019)
Introduction. Two factors of metal turning are compared: the dissipated temperature and the power of irreversible transformations in the material of the product and the tool. The paper is devoted to the issues of mathematical modeling of their link.Materials and Methods. The mathematical apparatus is based on the modification of the Volterra equation which involves the use of double integral. It shows how the thermal energy released earlier during cutting affects the current state of temperature in the tool-to-work contact zone. In addition to the proposed new basic mathematical model, the processing effect of the observed data on the power of irreversible transformations and the measured temperature in the tool-to-work contact zone under metal turning are used. The experiments were carried out on 1K625 machine and STD.201-1 stand. A specialized software tool for processing information arrays describing the processes occurring during cutting (reaction forces, tool vibrations and power of irreversible transformations) was created in the Matlab package. The same tool has performed the temperature calculation in the tool-to-work contact zone.Research Results. The procedure of parametric identification of the proposed basic mathematical model is carried out. The resulting model showed a high degree of proximity of the experimental data on the temperature in the cutting zone and the simulated level of thermal energy; but in the initial section of the measurable temperature dependence, the results of these two approaches are in rather poor agreement. This can be explained by an error of the experimental temperature measurement based on the estimate of the thermoelectromotive force (thermal EMF) output which is generated as a result of the dynamic thermocouple formation in the tool-to-work contact zone.Discussion and Conclusions. The proposed mathematical model enables to adequately describe the conversion of the mechanical component of the cutting energy into the thermal component through the indicator of the total output power of the mechanical interaction in the cutting zone for all the processing time.